Contribution of Oswaldo Paulo Forattini to public health: analysis of scientific production - Juliana Gonçalves Reis; Keilla Miki Kobayashi; Helene Mariko Ueno; Cristiane Martins Ribeiro; Telma Abdalla de Oliveira Cardoso
ABSTRACT OBJECTIVE To analyze the main characteristics of the scientific production of Oswaldo Paulo Forattini, researcher and, for 40 years, editor of Revista de Saúde Pública. METHODS Descriptive study with bibliometric approach conducted in three steps. (1) identification of bibliographic records using the following search strategy: "Oswaldo Paulo Forattini" OR "Forattini OP" OR "Forattini" up information sources Google Scholar, Web of Science, and PubMed, in July 2016, which retrieved 867 records. (2) composition of research corpus, in which we included 351 bibliographic records of articles, books, book chapters, editorials, book reviews, informative notes and annual reports of the RSP and excluded 516 duplicates and acknowledgement notes, obituary notes, and nonretrievable citations. (3) data organization and analysis, in which we built databases for descriptive analysis and development of the MeSH coauthors and terms networks in VOSviewer software. For analysis of editorials, three reviewers read the full text of each editorial and categorized them according to subject, historical context and perspectives, relating them with historical milestones. RESULTS Forattini's scientific production occurred from 1946 to 2009, most consisting of articles (n = 218; 62.1%), editorials (n = 43; 12.3%), and books (n = 13; 3.7%). The main subjects were Culicidae (36.8%), Triatominae (12.5%), and Epidemiology (10.0%). The coauthors of articles were his professors, colleagues of his generation, and graduate students. His editorials addressed critical reflections on the production of knowledge, research priorities, and factors that contributed to or hindered progress. The scope of subjects is broad, referring to socioeconomic and scientific development, public health issues in developed countries, or global health. CONCLUSIONS The analysis shows Forattini's commitment with public health, research with vectors, training of researchers, and scientific communication.